Deal! the bottom line of business English : reference book - D'Haens, Adriaan, 1984-; Du Pont, Olaf, 1977-; Jacobs, Geert, 1966- (Leuven : Acco, 2012)
Deal! is a comprehensive pre-work Business English course for speakers of Dutch. It includes a reference book, featuring vocabulary, skills and grammar, as well as a course book, focusing on oral and written communication. This reference book contains concise coverage of the most essential grammatical structures in Business English as well as different levels of practice focusing on those issues that are particularly difficult for speakers of Dutch. In addition, there is an extensive skills section on a wide range of communicative functions, from agreeing and disagreeing to chairing discussions and managing the Q&A at the end of a presentation. Special attention is paid to pronunciation and the use of language resources. Finally, the reference book includes a vocabulary section featuring both a basic list and more specialized glossaries.
Handboek bij cursus 'Economisch Engels I' (Geert Jacobs)
Keywords: Zakelijk Engels